2020
DOI: 10.1002/er.6305
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fe‐Ni‐Mg catalytic activities for hydrogen‐rich gas production from biomass pyrolysis

Abstract: We investigate the various roles of MgO in Fe-Ni-Mg catalytic system in the catalytic pyrolysis of pine needle biomass in a fixed bed reactor. And the change of productions was discussed to reveal the various roles of MgO at 750 C. We found that in the presence of MgO, hydrogen content was enhanced. And the variation in the Mg/3 Fe 1 Ni mass ratios indicated that MgO could act as a promoter at 750 C, and a catalyst at Mg/3 Fe 1 Ni ratio of <1, and >1, respectively. Moreover, the impact of temperature and heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Figure 3 showed that CO was evolved from pyrolysis of PWR at ≥300°C, and the evolution of CO could be ascribed to deoxygenation from a polymeric backbone of PWR 40 . One of the interesting observations is that CO formation by means of deoxygenation lasted even at ≥500°C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 3 showed that CO was evolved from pyrolysis of PWR at ≥300°C, and the evolution of CO could be ascribed to deoxygenation from a polymeric backbone of PWR 40 . One of the interesting observations is that CO formation by means of deoxygenation lasted even at ≥500°C.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 3 showed that CO was evolved from pyrolysis of PWR at ≥300 C, and the evolution of CO could be ascribed to deoxygenation from a polymeric backbone of PWR. 40 One of the interesting observations is that CO formation by means of deoxygenation lasted even at ≥500 C. Such observation offers two important messages. First, the continuous mass changes observed from the TGA tests of PW and PWR (Figure 2) at ≥500 C are ascribed to CO evolution through deoxygenation.…”
Section: Pyrolysis Of Pwrmentioning
confidence: 99%
“…This is an advantage for bioplastic products because it mitigates the problems of climate change and global warming. 7 Additional to bioplastics, valorization of organic biomass can led us to obtain sustainable and valuable materials, such as crosslinking agents, chemicals and fuels, 8 for example, raw materials for bio-hydrogen production, 9 solar cells, 10 wastewater treatment 11 and solar-steam-assisted desalination, 12 to name a few. In fact, biomass also has great potential in the functional materials field of high performance.…”
Section: Introductionmentioning
confidence: 99%